Evaluation of antimicrobial activity in products containing Neem oil - Fernandes, Sara (2015)
Neem oil is obtained from seeds of Azadirachta indica, which present 30 to 50% (w/w) of oil per seed. Neem oil has been associated with a great diversity of beneficial properties, namely antimicrobial, anti-inflammatory and insecticide. Information concerning the antibacterial activity of Neem oil is scarce. Although the existing studies have demonstrated activity against both Gram+ and Gram- bacteria, the results are in some cases contradictory and do not include a significant number of organisms, namely organisms associated with skin infections.